Comparison Analysis of Seismic Base Shear 23 Regencies in Aceh Province Based on SNI 03-1726-2012 and SNI 03-1726-2019 - Rahmaini Rahmaini; Fitri Arianggi; Maizuar Maizuar; David Sarana; Khairullah Yusuf (Master Program of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2022)
Aceh is one of the most earthquake-prone regions in Indonesia. It is, therefore, essential to design seismic resistance structures according to applicable standards. To reduce damage to building structures, the Indonesian government has updated the seismic-resistant design code for building and non-building structures. The seismic resistant design standard has been updated from SNI 03-1726-2012 to SNI 03-1726-2019 due to a significant change in spectrum response data. The purpose of this study was to evaluate and compare the impacts on the seismic base shear and the cross-sectional area of columns, beams, and tie beams of buildings in 23 regencies in Aceh Province based on SNI 03-1726-2012 and SNI 03-1726-2019. A typical five-story office building with medium-type soil is used in the study. For structural analysis, a particular moment-resistant frame was considered. The determination of the design response spectra is carried out by using coordinates and soil types through the website “indo spectra”. The method used is spectrum response analysis. Some different requirements in the two standards include the spectrum response curve, mass participation, and dynamic base shear. The study’s results revealed that the dynamic base shear in Sabang City had grown by 192.05 percent. Aceh Barat Daya Regency was observed to have the smallest increase in dynamic base shear, which was only 8.16 percent. The required cross-sectional area of structural columns, beams, and tie beams in Sabang City increased by 96%, 40%, and 44.44%, respectively; in the meantime, the required cross-sectional area of columns, beams, and tie beams in several regencies in Aceh province remained unchanged.